Industrial Training Report: Library of Politeknik Sultan Abdul Halim Mu'adzam Shah (POLIMAS) / Norfadzliani Mohd Fauzi - Mohd Fauzi, Norfadzliani (Faculty of Information Management, 2018)
This practical report was produce by a student of Bachelor of Science (Honours) library and information management (IM244) semester seven from faculty of Information Management, University Teknologi Mara on Politeknik Sultan Abdul Halim Mu'adzam Shah Library. This report paper is about the industrial training activities done by the trainee at Sultan Abdul Halim Mu'adzam Shah Library. This report based on the information from Politeknik Sultan Abdul Halim Mu'adzam Shah Library background and special project where the trainee had been placed for within 5 month. The industrial training focused on the book technical processing in the library and several of outside activities.